Effect of Combinations of Cryoprotectants and Freezing Rates on Cryopreservation of the Spermatozoa of Striped Catfish, Pangasianodon hypophthalmus (Sauvage, 1878) - Samorn Ponchunchoovong; Sunai Plime (Agriculture and Natural Resources, 2010)
Two experiments were carried out involving sperm cryopreservation of striped catfish, Pangasianodon hypophthalmus,. In the first experiment, the effects of combinations of cryoprotectants (dimethyl sulfoxide (DMSO 10%), dimethyl acetamide (DMA 10%) and methanol (5%)) were investigated. The combination of cryoprotectants involving DMSO (10%) + DMA (20%) had the highest fertilization rate of 59% (99% of control), followed by DMA (20%) + MeOH (5%) and DMSO (10%) + DMA (10%). These results were not significantly (p>0.05) different from the control. The percentage among treatments of viability and motility was lower than that of the control treatment (p<0.05). In the second experiment, each combination of cryoprotectants from the first experiment that had produced excellent fertilization rates (10% DMSO + 10% DMA, 10% DMSO + 20% DMA and 20% DMA + 5% MeOH) was mixed with 0.9% NaCl as extender and the effects of four freezing rates at 5, 10, 20 and 40°C min-1 on the cryopreservation of striped catfish were investigated. The highest fertilization rate was 75% (98% of control) resulting from 5°C min-1 using the combination of DMSO and DMA (10%). The freezing rates of 5 and 10°C min-1 yielded a similar fertilization percentage with the control (p>0.05). The outcomes from this study indicated that the combination of cryoprotectants used (5% MeOH and 20% DMA) increased the fertilization percentage compared with using 5% MeOH alone and also indicated that increasing the freezing rate up to 40°C min-1 decreased the fertilization rate of striped catfish sperm.